PEMIKIRAN DAN PERANAN SAYYID IDRUS BIN SALIM ALJUFRI TERHADAP PERKEMBANGAN PENDIDIKAN ISLAM DI MANADO - Rasyid, Lisa Aisyiah; Supriadi, Supriadi; Aisa, Siti (Institut Agama Islam Negeri (IAIN) Manado, 2018)
Abstrack. As one of the scholars of the hadramain who played an important role in the development of islamic education in the eastern region of Indonesia, It is important to understand how the thinking and role of sayyid, the iraniacal bin salim aljufri, especially in the tower of the thousand churches, the city of manado. When Indonesia is beset by two themes of political persecution, fierce debate over islamic relations and countries between